USING DIGITAL TECHNOLOGIES TO IMPROVE VISUAL ARTS EDUCATION FOR GRADES 5–7 IN GENERAL SECONDARY SCHOOLS - Xamidova Dildora Muhiddin qizi (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Annotation: This article examines the implementation of digital technologies in teaching visual arts to students in grades 5–7 in general secondary schools. It explores interactive lessons, multimedia applications, and digital drawing tools as methods to enhance creativity, visual literacy, and practical artistic skills. The study highlights the benefits of digital technologies in fostering student engagement, promoting individualized learning, and encouraging collaborative art projects.